The Association of Central Corneal Thickness and Intraocular Pressure Measures by Non-Contact Tonometry and Goldmann Applanation Tonometry among Glaucoma Patients - Kyei, Samuel (Ethiop J Health Sci, 2020)
BACKGROUND: The aim of this study was to determine whether Central Corneal Thickness (CCT) is associated with intraocular pressure measurement (IOP) with a Non-contact tonometer and the Goldmann applanation tonometer in glaucoma patients. MATERIALS AND METHODS: The study involved two hundred and thirty-two eyes of clinically diagnosed glaucoma patients receiving care at a referral facility. IOP measurements were obtained using both the Non-Contact Tonometer (NCT) and Goldmann Applanation Tonometer (GAT). The association between age, ethnicity, and CCT, as well as CCT on the measures of NCT and GAT, were analyzed. RESULTS: There were 64(55.2%) males and 52 (44.8%) females and their ages ranged from 18 to 85 years (mean age = 47.72; SD ± 15.75 years). There was a weak positive correlation between the CCT and NCT findings in the right eye (r = 0.19, n = 116, p < 0.05) and in the left eye (r = 0.25, n = 116, p < 0.05). However, there was no correlation between CCT and GAT measurements. Age had a significant correlation with CCT while gender and ethnicity had no significant correlation. CONCLUSION: The study found a significant association between CCT and NCT. However, there was no significant association between CCT and GAT. CCT had an association with age but independent of gender and ethnicity since there was no significant relationship between these variables.